THE COORDINATION OF ADMINISTRATOR OF SUB-DISTRICT TO SUPPORT THE EFFECTIVENESS OF DEVELOPMENT IN BORONUBAEN VILLAGE AT NORTHERN BIBOKI (2017) - Pereira, Tomas; M. Tamunu, SU., Dr. Lenny; M.Si., Dr. Nursalam, (IJRDO - Journal of Applied Management Science, 2018)
Implementation of the National Development Activities in the State of the Republic of Indonesia is actually one of the efforts to realize the ideals of the nation that is the creation of prosperous and prosperous society welfare based on the Constitution (Pembukaan UUD 1945). The achievement of these ideals is implemented in a systematic and integrated in   form of operational development in harmony with   phenomenon and dynamics that occur in society life.Coordinating mechanisms in   implementation of development to continue to direct its activities towards the achievement of these development goals and reduce inefficiencies and destructive conflicts. Coordination is intended for the implementing the development the apparatus should accumulate all of human resources and other resources owned. Successful implementation of development depends on the ability of officials responsible for   implementation of development to arrange various resources in achieving a goal. The research method used is qualitative research, with   qualitative data which means directly taken from research location used as actual data. From   actual data obtained as data to support the process of writing in this study. The method used in data collection the author uses observation, documents and interviews. From the results of data analysis conducted by the authors pointed out that   success of development in  Boronubaen village  still far from   programmed by the central government entrusted directly to local government, this is not appropriate and lack of ability so that a constraint in  implementation of development.From the results of this study, it is suggested to the administrator of sub district to   pay attention in implementation of development, especially in   Boronubaen village. To cooperate with NGOs in paying attention to community development and appreciation regarding   ability and economy that negatively affect the effectiveness of development implementation. Also to   community, in order to maintain   development that has been implemented because it is a shared responsibility.